DEVELOPMENT OF TEACHING MATERIALS ESD (EDUCATION FOR SUSTAINABLE DEVELOPMENT) IN COACHING SKILLS OF SELF CHILDREN WITH INTELLECTUAL CHALLENGES IN SMA LB C IN JAKARTA - Nadiroh Nadiroh; Irah Kasirah (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2015)
The purpose of this research is to develop teaching materials ESD (Education for Sustainable Development) in subjects Self Development skills in a special program of vocational skills such as making skills of the rest of the patchwork mat and look for alternative learning model development Self Development skills required of teachers in accordance with the child's ability mentally retarded that still form an outline of the learning program.The research was conducted in SLB C East Jakarta. The subjects of research that high school teachers and students mentally retarded LB C. Outcome or product part of this research is the study of ESD (Education for Sustainable Development) in subjects Self Development skills in a special program of vocational skills makedoormats from the rest of the patchwork.The results of this study are expected to contribute to the implementation of innovative teaching model for teachers SLB C through the development of teaching materials ESD (Education for Sustainable Development) in practice the skillsself help Mentally Retarded Children in order to achieve self-reliance to improve the quality of life of chldren with intellectual challenges.